Diagnosing preclinical and clinical Alzheimer's disease with visual atrophy scales in the clinical practice - Karen Luiza Ramos Socher; Douglas Mendes Nunes; Deborah Cristina P. Lopes; Artur Martins Novaes Coutinho; Daniele de Paula Faria; Paula Squarzoni; Geraldo Busatto Filho; Carlos Alberto Buchpiguel; Ricardo Nitrini; Sonia Maria Dozzi Brucki (Arquivos de Neuro-Psiquiatria)
Background Visual atrophy scales from the medial temporal region are auxiliary biomarkers of neurodegeneration in Alzheimer's disease (AD). Therefore, they may correlate with progression from cognitively unimpaired (CU) status to mild cognitive impairment (MCI) and AD, and they become a valuable tool for diagnostic accuracy.